How corporate social responsibility affects brand equity and loyalty? A comparison between private and public universities - Poh Ling Tan; S. Mostafa Rasoolimanesh; Govindaraju Manickam (Heliyon, 2022)
This study compares the direct and indirect effects of corporate social responsibility (CSR) on brand equity and brand loyalty between public and private universities. Additionally, this study compares the direct effect of CSR on brand reputation; brand reputation on brand equity and loyalty; and the role of brand reputation as a mediator between public and private universities. Data were collected from one public and one private university in Malaysia, with 600 questionnaires collected from students of Taylor’s University and the University of Malaya, both top private and public universities in Malaysia, respectively. The measurement model and hypothesis testing were assessed using partial least squares - structural equation modelling. The findings showed positive and significant effects for CSR on reputation, brand equity, and brand loyalty, either directly or indirectly, for private and public universities. There were significant disparities between public and private institutions in the direct and indirect impacts of CSR on brand loyalty, as well as the effects of brand reputation on brand loyalty. This study makes a unique theoretical contribution to the literature by comparing the direct and indirect effects of CSR on brand reputation, brand equity, and brand loyalty between public and private universities; in assessing the mediation role of brand reputation between CSR, brand equity, and loyalty through brand reputation; and in comparing this mediation effect between public and private universities. Furthermore, this research has practical implications for both public and private higher education institutions as they create their branding strategy.